PENGARUH INFESTASI CACING SALURAN PENCERNAAN TERHADAP BOBOT TUBUH KAMBING SABURAI PADA KELOMPOK TERNAK DI KECAMATAN GEDONG TATAAN, KABUPATEN PESAWARAN, PROVINSI LAMPUNG - Segara, Rendi Bayu; Hartono, Madi; Suharyati, Sri (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2018)
This research aims to know the effect about gastrointestinal worm infestation on body weight of goat Saburai in Gedong Tataan District Pesawaran Lampung Province. This research was conducted in August - September 2017. Testing of Mc Master and Sedimentation Test at Parasitology Laboratory, Lampung Veterinary Center. This study uses 83 goats Saburai Goat found in livestock group Gedong Tataan district Pesawaran Regency Lampung Province. The data were made in tabulation and analyzed by t-test. The results indicate that goat Saburai infestation by gastrointestinal worms in the group of Gedong livestock there are ± 52 positive samples infected with the gastrointestinal worms or 62.7% total population. Based on the results identification type gastrointestinal worms are Haemonus sp (50.66%), Strongyloides sp (25.3%), Oeshophagostomum sp (22.9%), Trichostongylus sp (18.1%), Bunostomum sp (7, 3%) moniezia sp (3,6%) Mecistocirrus sp (1,2%). The result of t-test showed that gastrointestinal infestation had significant effect (P <0,01) on body weight goat Saburai with difference body weight 6,39 kg at age ≥ 1 year and 8,10 kg at age <1 year. Keywords: infestation, Saburai goat, body weight